Hipervulnerabilidade, publicidade e consumismo: uma reflexão sobre os adolescentes de escolas públicas e privadas de Pelotas/RS - Vasconcellos, Estela Maris Foster (2019)
The hypervulnerability, a recent concept of jurisprudence and doctrine, is characterized when the consumer, due to a peculiar situation, has his/her vulnerability aggravated. Advertising in the contemporary society progresses to some protective boundaries surrounding the adolescents, which, according to the Code of Consumer Protection may be characterized as misleading or abusive advertising. Misleading is the one which, among other elements, is able to induce the consumer to an error. Abusive is the one which makes use of his/her vulnerability, having in mind, among other characteristics, the age; it aims at creating a certain lifestyle stimulating the acquisition of products or services. The purpose of the research is to analyze if the hypervulnerability can be considered in different levels, when studied based on personal conditions, within the same hypervulnerable group. The personal conditions refer to access time to the internet and the attitude of thinking about the need of acquisition of a product or service when facing a purchasing situation. The specific purposes are: establish the relationship between hypervulnerability and consumerism in the contemporary society; point out the relevant legislation to the legal protection of adolescents concerning the advertising aimed at them; compare the statistical data resulting from an empirical research concerning the teens from public schools with the teens from private schools. Based on the hypothetical-deductive approach, it has been investigated if the teens enrolled at the public school and at the private school are found in distinct levels of hypervulnerability. The research tests the hypothesis that as well as new vulnerabilities arise, the same occurs in terms of differences in the level of hypervulnerability of the consumer. This hypothesis is justified when we outline an approximation with the social markers of difference. The methodological procedures used were: bibliographic research (Capes Thesis and Dissertations Catalog); empirical research (with an application of a questionnaire for the students, through an Informed Consent Form signed by the parents). In order to safeguard confidentiality and anonymity, the questionnaire was not identified. The research project was submitted to the Ethics Committee, given the terms of the Resolution n. 510/2016. In the last phase the empirical data obtained was described and analyzed. The research showed that the adolescents spend many hours online daily, whether they are from public or private school, not presenting differences concerning their access time to the internet. Both groups are exposed to advertisements many hours a day. Public school teens mentioned, mostly, a tendency of always thinking whenever they face a purchasing situation; an opposed attitude identified in private school students. When compared concerning their attitudinal aspect of thinking about the need of a product or service, before a purchasing situation, the adolescents presented a certain difference in the level of hypervulnerability; a situation which shall be observed and therefore complementary studied should be carried out. Also, other biases should be analyzed so that other approximations with the social markers of difference can point out to other differences in the levels of hypervulnerability. More studies are necessary so that other hypotheses can be tested.